1997
DOI: 10.1016/s0741-5214(97)70014-4
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal comparison of dialysis access methods: Risk factors for failure

Abstract: The patency rate for PTFEs is similar to that for AVFs, but AVFs require fewer revisions. When replacing a failed access graft, the risk of PTFE failure increases with the number of prior unsalvageable PTFE shunts. PDCs have excellent patency rates, but failure rates are doubled in patients with diabetes. Because of poor patency rates and inadequate dialysis flow rates, SIHCs should be avoided when possible. Reporting methods dramatically affect apparent patency rates, and reporting standards are needed to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
1
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(146 citation statements)
references
References 28 publications
(14 reference statements)
5
132
1
8
Order By: Relevance
“…The thigh graft thrombosis rate of 1.58 per patient-year compares favorably to that reported for tunneled dialysis catheters (3.0 to 3.2 per patient-year, or 8.1 to 8.8 per 1000 patient-days) (28,33). The cumulative thigh graft survival rate at 1 yr (62%) is substantially higher than the corresponding 9% rate reported for tunneled dialysis catheters (34). Finally, the median dialysis blood flow delivered by grafts is substantially higher than that obtained with catheters, thereby enhancing dialysis adequacy (6).…”
Section: Discussionmentioning
confidence: 51%
“…The thigh graft thrombosis rate of 1.58 per patient-year compares favorably to that reported for tunneled dialysis catheters (3.0 to 3.2 per patient-year, or 8.1 to 8.8 per 1000 patient-days) (28,33). The cumulative thigh graft survival rate at 1 yr (62%) is substantially higher than the corresponding 9% rate reported for tunneled dialysis catheters (34). Finally, the median dialysis blood flow delivered by grafts is substantially higher than that obtained with catheters, thereby enhancing dialysis adequacy (6).…”
Section: Discussionmentioning
confidence: 51%
“…However, fistulas fail to mature at a higher rate than do grafts (2)(3)(4)(5). Therefore, when one includes failures to mature in calculating vascular access outcomes, the cumulative survival of fistulas and grafts is similar ( Figure 1A) (2)(3)(4)(5)(6)(7)(8)(9)(10). However, once they are successfully used for dialysis, grafts require far more interventions than do fistulas to maintain long-term patency for dialysis.…”
Section: Why Should We Increase Fistula Use?mentioning
confidence: 99%
“…(3) Puncture of dialysis grafts and fistulae could cause platelet thrombi and cytokine release (27). (4) Figure 6. From pathogenesis to pathology to novel therapies.…”
Section: Pathogenesis Of Avf and Ptfe Graft Failurementioning
confidence: 99%
“…Primary nonfunction or rates of failure to mature up to 50% have been reported by some centers, particularly when an aggressive fistula placement policy is enforced (5). Therefore, primary patency rates as low as 43% (6) and 56% (7) have been reported for AVF in some instances. In addition, Miller et al (5) showed a higher primary nonfunction rate in forearm fistulae as compared with upper arm fistulae (59 versus 34%).…”
Section: Introduction and Types Of Hemodialysis Vascular Accessmentioning
confidence: 99%